RAZ JESZCZE: DOPUSZCZENIE DO SAKRAMENTÓW ROZWIEDZIONYCH, KTÓRZY ZAWARLI NOWE MAŁŻEŃSTWO? CIERNISTY I KOMPLEKSOWY PROBLEM - Kasper, Walter (Warszawskie Studia Pastoralne, 2016)
Kasper’s article refers to his earliest statement during Consystorium in February 2014. He explicates some subjects connected with divorced people who got civil married again.